Islamic accountability framework in the zakat funds management - Saad, Ram Al Jaffri; Abdul Aziz, Norazita Marina; Sawandi, Norfaiezah (Elsevier Ltd., 2014)
The purpose of this paper is to provide a discussion on the Islamic accountability in the zakat funds management.The in-depth understanding over the accountability system and practices of zakat institutions may assist to identify the underlying factors that lead to inefficiency in zakat distribution.The article is primarily theoretical and conceptual in nature.The paper discusses the suitability and applicability of the Islamic accountability framework in the zakat funds management.The Islamic accountability framework presented here, however, is an early attempt in understanding and assessing the effectiveness of accountability practices in managing zakat funds.